2018
DOI: 10.1038/emm.2017.248
|View full text |Cite|
|
Sign up to set email alerts
|

Rab25 augments cancer cell invasiveness through a β1 integrin/EGFR/VEGF-A/Snail signaling axis and expression of fascin

Abstract: The small GTP-binding protein Rab25 is associated with tumor formation and progression. However, recent studies have shown discordant effects of Rab25 on cancer cell progression depending on cell lineage. In the present study, we elucidate the underlying mechanisms by which Rab25 induces cellular invasion. We demonstrate that Rab25 increases β1 integrin levels and subsequent activation of EGFR and upregulation of VEGF-A expression, leading to increased Snail expression, epithelial-to-mesenchymal transition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…Indeed, treatment with a stapled peptide, which inhibits interactions between Rab25 and its effectors, suppresses the proliferation and migration of ovarian cancer cells in which Rab25 functions as an oncogene, but augments the aggressive phenotype in breast cancer cells in which Rab25 functions as a tumor suppressor . Furthermore, Jeong et al found that the oncogenic activity of Rab25 in ovarian cancer cell lines accrued through Rab25‐dependent increases in β1 integrin levels, which subsequently activated EGFR, upregulated VEGF‐A expression, and increased Snail expression, ultimately promoting cancer cell invasion . These data suggested that while Rab25 regulates trafficking in many cells, the actual patterns of integrin regulation are dependent on tumor context.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, treatment with a stapled peptide, which inhibits interactions between Rab25 and its effectors, suppresses the proliferation and migration of ovarian cancer cells in which Rab25 functions as an oncogene, but augments the aggressive phenotype in breast cancer cells in which Rab25 functions as a tumor suppressor . Furthermore, Jeong et al found that the oncogenic activity of Rab25 in ovarian cancer cell lines accrued through Rab25‐dependent increases in β1 integrin levels, which subsequently activated EGFR, upregulated VEGF‐A expression, and increased Snail expression, ultimately promoting cancer cell invasion . These data suggested that while Rab25 regulates trafficking in many cells, the actual patterns of integrin regulation are dependent on tumor context.…”
Section: Discussionmentioning
confidence: 99%
“…An important event underlying metastasis is EMT. Extensive literature has established links between transcriptional factors (EMT-TFs) such as Snail1 [ 107 , 108 ], ZEB [ 109 ], Twist [ 110 , 111 ] and metastatic processes of cancer cells e.g. E-cadherin downregulation, angiogenesis, and intravasation [ 107 ].…”
Section: Stromal Metamorphosis and Metastasis: A Story Of Reciprocitymentioning
confidence: 99%
“…The effect of AGPS on the pathway network was analyzed in human glioma cells by sequencing and bioinformatics analysis, and it was discovered that AGPS silencing regulated tumor-related signaling pathways, such as the PI3K/Akt, Toll-like receptor, focal adhesion and VEGF signaling pathways. These aforementioned results were further validated by RT-qPCR, where significantly upregulated expression levels of THBS1 and ITGA11, and downregulated expression levels of SPP1, VEGFA, EGFR, IL7R, CXCL8, PTGS2 and SDC4, were all identified; all of these are crucial genes involved in the aforementioned signaling pathways, and have been found to serve roles in tumor metastasis and angiogenesis (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 72%